The LABEC (Laboratorio di tecniche nucleari per l’Ambiente e i BEni Culturali - Laboratory of Nuclear Techniques for the Environment and Cultural Heritage) - Fedi, Mariaelena; Mandò, Pier Andrea (Il Colle di Galileo, 2022)
The history and activities of the LABEC are presented, from the first work carried out on the KN3000 accelerator at the Garbasso building, to the move to the new site in Sesto Fiorentino with the installation of the new accelerator, to the present day.